THE PROGRAM OF MEASLES ELIMINATION IN EUROPE - Lončarević, Goranka; Pekmezović, Tatjana (Medicinski podmladak, 2023)
THE PROGRAM OF MEASLES ELIMINATION IN EUROPE Abstract The use of a safe and effective measles vaccine in national immunization programs has resulted in a reduction in the number of deaths from the disease, although measles remains one of the leading causes of death in children under 5 years of age in underdeveloped and developing countries. After the successful eradication of smallpox, as well as the results achieved in the eradication of poliomyelitis at the global level, the process of measles elimination was initiated using the previously known strategies. In both American regions of the World Health Organization (WHO), the elimination of measles has been successfully verified, while in the WHO European Region, up to 2020, elimination has been verified in 29 out of 53 countries. The main challenges in the process of measles elimination are reaching and maintaining high immunization coverage, reaching and maintaining the values of surveillance indicators, implementing additional immunization of unvaccinated and incompletely vaccinated persons, solving serious problems such as the occurrence of measles epidemics in vulnerable groups, endemic maintenance of the disease, re-establishment virus transmission, determination of chains of transmission, genotyping of agents, impact of measures to control the COVID-19 pandemic. Bearing in mind the mentioned problems, the WHO has decided to postpone the elimination of measles in the WHO European Region to the year 2030.